The Impact of Digital Technologies and Platforms on the Transformation of International Management: Challenges and Prospects for Business - Osaulenko, О. H.; Hrynchak, N. А.; Horobets, О. О. (Statistics of Ukraine, 2025)
This article provides a comprehensive analysis of the impact of digital transformation on the system of international management, which is undergoing fundamental changes under the pressure of globalization, rapid technological progress, and evolving customer expectations across different countries. Digitalization is considered not merely as the implementation of separate technological solutions but as a strategic process that reshapes the very essence of conducting international business – from models of internationalization and human resource management to business process organization, logistics, marketing, and communications. Special attention is given to the evolving role of international managers, who must navigate complex digital ecosystems, coordinate virtual teams, adapt strategies to the cultural and institutional contexts of various countries, ensure cybersecurity, manage change, and implement innovations. The importance of developing digital competencies, managerial skills in working with big data, and the ability to balance local specificity with a global vision is emphasized. The article explores how digital platforms are altering the logic of international expansion by creating conditions for borderless business while simultaneously generating new challenges – such as intensified competition, distribution channel conflicts, reliance on reputational signals, regulatory instability, and the need for flexible ecosystem management. Key mechanisms for achieving international success are analyzed, including the use of data analytics, artificial intelligence, cloud-based solutions, localization of digital products, and adaptation of business models to the demands of foreign markets. It is substantiated that digital transformation is a critical driver in the evolution of international management. It requires a revision of approaches to strategic planning, company structure, value chain configuration, and the development of long-term stakeholder relationships on a global scale. The successful implementation of digital internationalization depends on the ability of leaders to integrate digital technologies with managerial practices and adapt to the complex dynamics of the international environment.